Acupressure for older people with cognitive impairment: a systematic review and meta-analysis of randomized controlled trials - Zhang, Hongkun; Zhu, Luwen; Wu, Minmin; Song, Wenjing; Li, Jinting; Tang, Qiang; Zhang, Jiongliang (Frontiers in Psychiatry, 2025)
IntroductionCognitive impairment (CI) is becoming more common in the older population (≥60 years old) and has become a burden and challenge in an aging society. Acupressure is a non-invasive, safe, and cost-effective modality in Chinese medicine. Its therapeutic effects are achieved by stimulating specific points to restore balance in the flow of qi along the meridians, thereby enhancing the physiological functions of body systems and organs. This study aimed to conduct a meta-analysis to evaluate the effects of acupressure on cognitive function, mood, and activities of living (ADL) in older adults with CI.MethodsA comprehensive database search was performed using PubMed, Embase, Cochrane Library, Web of Science, Sinomed, CNKI, Wanfang, and VIP databases to identify randomized controlled trials (RCTs) investigating the effects of acupressure versus non-acupressure in elderly patients with CI. We searched on June 6, 2024 for trials that met our predefined inclusion and exclusion criteria from database construction to the present. An additional search was conducted from June 6, 2024 to March 16, 2025. Data were extracted, the literature was reviewed, and the methodological quality of the included trials was assessed. A meta-analysis was performed using StataSE version 16.ResultsThe meta-analysis included 1,149 patients from 15 RCTs. Results showed that compared with the control group, cognition (mean difference [MD] = 2.36, 95% confidence interval = 1.71 to 3.00, P < 0.001, I² = 41.8%), agitation (MD = -1.51, 95% confidence interval = -2.52 to -0.50, P = 0.003, I² = 0%) and depression (standardized mean difference [SMD] = -1. 33, 95% confidence interval = -1.80 to -0.86, P < 0.001, I² = 32.2%) improved. However, no significant differences were observed in ADL.ConclusionThis systematic review provides valuable evidence for using acupressure to improve cognitive function and mood in older adults with CI. In the future, acupressure may improve cognition and mood in this demographic. More studies on acupressure are needed to generate stronger and more robust evidence.Systematic review registrationPROSPERO, identifier: CRD42024556579.